Culture's causes: the next challenge. Issue 4 (5th October 2015) - Hofstede, Gert Jan
Abstract : Purpose: – The purpose of this paper is to argue that in cross-cultural and strategic management, we must pay attention to the processes creating and maintaining culture. How can everyday interactions give rise to national, "deep" cultures, recognizable across centuries, or organizational cultures, recognizable across decades? Design/methodology/approach: – This is a conceptual paper using the evidence provided by research about cultural patterns, and using sociological status-power theory to explain the causation of these patterns. Emergence, also called self-organization, is introduced as mechanism connecting individual-level causation with resulting system-level patterns. Cases are used to illustrate points. Findings: – Simulation gaming and computational social simulation are introduced. These methods allow "growing" a system, thus allowing to experiment with potential interventions and their unanticipated effects. Research limitations/implications: – This essay could have major implications for research, adding new methods to survey-based and case-based studies, and achieving a new synthesis. Strategic management today almost invariably involves cross-cultural elements. As a result, cross-cultural understanding is now strategically important. Practical implications: – The suggestions in this essay could lead to new collaborations in the study of culture and organizational processes. Examples include team formation, negotiation, mergers and acquisitions, trans-national collaboration, incentive systems and job interviews. Social implications: – The suggestions in this essay could contribute to our ability of proactively steering processes in organizations. In particular, they can provide a check to the notion that a control measure necessarily results in its intended effect. Originality/value: – The synthesis of biological, sociological and cross-cultural psychological viewpoints with design-oriented method, using games or social simulations as research instruments, is original in the field.